A Facile Method for the Titration of Organolithium Reagents using Naphtylamine or Naphtylmethylamine as Indicators - Cabezas Pizarro, Jorge A. (2019)
A simple method for the titration of alkyllithiums with sec-butanol, using naphtylamine or naphtylmethylamine as color indicator, is reported. Both amines gave sharp-end points, easily determined by color changes from brown to yellow (naphtylamine) and from green to colorless (naphtylmethylamine). The accuracy of the determination was in accordance with the values obtained by a standard method.